Computation of phase and structural deformations in shape memory alloys. One-dimensional model. (2017) - Tikhomirova, Ksenia
Abstract: A phenomenological model describing phase and structural deformations in shape memory alloys (SMA) is developed. The model takes into account the loading history of the specimens and describes several phenomena caused by martensitic transformation with the use of the universal approach. Phase deformation is considered as a change in the length of the chain of series-connected structural elements: spherical austenitic and elongated martensitic elements. The experimental method of material constants identification is discussed.